OMSK REGION MIGRATION SECURITY. YOUTH ASPECT - A. M. Kiseleva (Вестник СибАДИ, 2018)
Introduction. The article considers the youth migration processes in the Omsk region, which lead to the migration security problem on Omsk territory. This process entails to the threats of the region economic development and requires adequate solution, since young people represent the most active category of the population in the vocational and labor aspect, and the main migration outflow is associated with it. Materials and methods. However, the regional statistics’ data and the conducted research based on the youth representatives’ overall survey reflect the negative trend and parameters of youth migration security. This suggests that the main reasons for the young specialists’ outflow are the need for a higher income compared to the proposed conditions of the regional economy, and a more attractive working place in terms of their professional capabilities’ realizing. Results. The results of the research show that the migration security problem should contribute to the attention increasing of the regional authorities to minimize the young people with higher educational outflow. Сonclusion. Therefore, the solution of this problem by the region authorities should focus on the measures of ensuring the necessary living standard for young people, increasing wages in key economy areas and improving the social and economic conditions for the Omsk region development.